The Impact of Islamic Banks Productive and Consumptive Financing on Indonesia Economic Growth - Nafi, Muhammad Hilmy Khoirun; Suwanan, Ahmad Fawaiq (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2024)
This research aims to determine the role of Islamic banks institution financial programs encourages the Indonesia's real economy. The financing variable is explained in more detail through the type of financing channeled, namely productive financing, consumptive financing, third-party funds (ID) as one of the sources of funds for financing distribution by Islamic banks, and gross fixed capital formation (GFCF) variables as control variables. Panel data regression is used in this research to investigate the influence of variables in 33 provinces in Indonesia in the period 2013-2023. It was found that the growth of productive financing, third-party funds, and GFCF had a significant positive effect on GRDP growth partially, while the consumptive financing growth variable had an insignificant negative impact. Simultaneously, all four independent variables successfully influence the dependent variable significantly. According to this study findings, researchers urge Islamic bank institutions to encourage the distribution of productive type financing to increase the productivity of economic activities in Indonesia, considering that most of the Islamic financing channeled is consumptive.